Peran Statistik dalam Mendukung Literasi Data Mahasiswa di Era Digital - Inung Diah Kurniawati; Andara Mashitoh (CV. ITTC INDONESIA, 2025)
Students, as representatives of the digital generation, are expected to possess adequate data literacy skills to manage, analyze, and convey data-based information in a critical and responsible manner. In this context, statistics serves as an important foundation in developing these skills. However, many students still face challenges in understanding and applying statistical concepts. This is due to several factors, such as a less applicable learning approach, low interest in statistics courses, and limited mastery of supporting technology. This study aims to identify various obstacles faced by students in utilizing statistics as a data analysis tool. Through a qualitative approach based on literature review, it was found that the gap between theory and practice, minimal use of technology, and a lack of integration between real-life contexts and statistics learning are the main factors hindering the effectiveness of statistics learning in higher education. Therefore, innovation in teaching methods, strengthening digital competencies, and a contextual approach are needed so that statistics can function not only as theory but also as a thinking tool that is applicable in students' daily lives.